CUSTOMER SERVICE ADMINISTRATIVE SYSTEM ABC AGENCY - Antarini Br Purba; Yulina SKom, MMSI Yulina SKom, MMSI (Jurnal Sistem Informasi, 2005)
Computer Use in the administration of companies, particularly in the consolidatedcustomer data and transaction data is something very important in the companynewspaper and magazine distributors, as a material for storing customer data andtransaction data, then the computer is necessary.To the writer tries to give a customer information system design activity continues tobe fast and accurate, thus created a customer data processing program withapplications Visual Basic 6.0 programming language. With the expectedcomputerized data - data that can be processed correctly, quickly and accurately.